Short communication: An outbreak of conversion disorder in a rural school in Western Nepal (Journal of Psychiatrists' Association of Nepal, 2024)
In Rastriya Madhyamik Vidyalaya, Banke district, Rampur, there was a sudden onset of conversion disorder affecting 53 students, most of them were school going young girls. The event started when a female student in exam hall was shaking, mumbling and had her hair covering her face. Such behaviors were rampant soon and over 30 students were exhibiting similar symptoms including tremors, shouting spells and abdomen pain. This led to immediate response from the school authorities together and we reached there after a call from the school authority. We isolated the affected students and observed, examined and found that they exhibited signs of mass hysteria rather than any organic disease.This communication shares the response strategies used to manage this outbreak effectively and also highlights the necessity of early intervention, mental health support and resilience building strategies to deal and prevent the mass hysteria in school setting.